Kajian Perkembangan Penggunaan Lahan Akibat Perkembangan Aktivitas Industri di Kota Parakan - Pratiwi Dwi Lestari; Rina Kurniati (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Parakan is a small town of the old kadipaten menoreh in Dutch colonialism, which is having a strategic location, where the line between jogyakarta's line and the northern coast line of java island and also between line of semarang and purwakarta, made parakan became the centre of market for food and tobacco trade from ancient times until now. In 2008, Parakan experienced in structural changes in addition to change the economic structures. The conversion in parakan from 2005-2017 also increased because of industrial development. The presence of industrial growth certainly affects the change in the characteristic of parakan. The method of analysis that used is a qualitative method analysis with qualitative descriptive and overlay map analysis techniques using arcgis software 10.4. Based on the analysis development of the cities, from the 2005 and 2017, have a tendency to change, which the land functions have increased in the city from 1990 to 2017. The number of parakan city settlements in 1990 was 202.64 ha and then increased to 259.97 in 2005 and 311,57 in 2017. Therefore, this study deals with the impact of  the development of industrial activities on its use.